A Incidence, Contributing Factors and Fetomaternal Outcomes of Placenta Previa: A Matched Case- Control Study among Mothers Delivered at Jimma Medical Center, Southwest Ethiopia.: Incidence, Contributing Factors and Fetomaternal Outcomes of Placenta Previa: - Belina, Sena (Ethiopian Journal of Reproductive Health, 2025)
Background: - Placenta previa is an abnormally positioned placenta in the lower uterine segment, which can partially or completely cover the cervix. It complicates approximately 3-5 per 1,000 pregnancies worldwide and is becoming more common due to increasing cesarean section rates. This condition is associated with maternal and neonatal morbidity and mortality. Therefore, investigating maternal and perinatal outcomes related to placenta previa is essential for recommending interventions and strategies. Objective: The objective of this study was to assess incidence, contributing factors and birth outcomes of placenta previa among mothers delivered in Jimma Medical Center Methodology: A facility based observational matched case-control study design was employed among a total of 450 samples from November 2020 to September, 2021. Controls are Matched with Cases with Age and Parity. Data was cleaned, coded, and entered into SPSS version 26.0 statistical software. Descriptive statistics was used to summarize categorical variables. Bi-variable and multivariable logistic regression was employed to identify association between dependent and independent variables. Adjusted odds ratio (AOR) with 95% confidence intervals and P value < 0.05 was considered statically significant. The results were compiled and presented in tables and graphs. Results: - The magnitude of Placenta Previa Observed was 15 in 1000 deliveries. Previous history of spontaneous incomplete abortion (AOR 11.06; 95% CI: 1.41, 86.82) is significantly identified risk factor. A need for blood transfusion (AOR: 15.69; 95%CI, 4.28, 57.53) , operation under general anesthesia (AOR 6.27, 1.74, 22.57) , hospital stay more than 4 days (AOR: 16.62 95%CI 6.78, 40.75) and Anemia with Hg < 11 g/dl (AOR; 8.22 95% CI 2.17, 31.05) are significantly identified maternal complications and admission to NICU of newborns of placenta previa (AOR; 10.95 95%CI 1.37, 87.32) is significantly identified neonatal complication with P < 0.05. Conclusions: Previous history of spontaneous incomplete abortion is significantly associated risk factors of placenta previa. Maternal complications associated with placenta previa are a need for blood transfusion, anemia with hg < 11 g/dl, exposure to general anesthesia and prolonged stay at hospital before delivery. Neonatal complication of placenta previa found was increased risk of admission to NICU.